Durable vanadium dioxide with 33-year service life for smart windows applications - Vu, Tuan Duc (2022)
The smart window that can regulate sunlight transmittance is one of the simplest solutions to reduce the massive energy consumption of heating, ventilation, and conditioning applications in building services. As a promising smart window material, vanadium dioxide (VO2) is severely limited in commercialization potential due to its instability in the operational environment. Protective layering to combat VO2 degradation often requires extra fabrication steps which can be complex and costly. We report a new strategy to fabricate VO2 nanorod nanocomposite thermochromic smart window with 33-year service life. By introducing seeding, a one-step high-powered impulse magnetron sputtering process is achieved which comprises of guided growth of VO2 nanorod embedded within amorphous V2O5 matrix. Furthermore, the unique nanorod structure with lowered transition temperature τc of 56.6 °C gives tunable solar modulation according to solar incident angle. This new strategy provides a solution to address VO2 Achilles’ heel, its instability, which could facilitate the applications of this near room temperature phase change material not limited in thermochromic smart windows.